Earnings Management As A Moderator On The Effect Of Information Asymmetry On The Cost Of Equity Capital - Fasihat, Dian Urna Fasihat; Iskandar, Rizkiana Iskandar (Dinasti Publisher, 2024)
To maximize the company's value, management must aim to reduce the Cost of Equity Capital (CEC) as much as possible. Investors will assume that the company's risk is low when the CEC is low, which in turn will enhance the company's value. However, the reality in Indonesia shows the opposite; the CEC of companies has been increasing year after year. Based on this phenomenon, it is necessary to examine the factors influencing CEC. Agency theory suggests that information asymmetry and earnings management can affect CEC. This study aims to test the direct effects of information asymmetry on CEC and earnings management on CEC, as well as the indirect effect of information asymmetry on CEC using earnings management as a moderating variable. The results of the data analysis show that information asymmetry affects earnings management and CEC. Furthermore, it was found that earnings management does not affect CEC. However, earnings management can moderate the relationship between information asymmetry and CEC